복수 배액관 삽입 시 발생한 의인성 대장 천공을 내시경 클립술로 치료한 1예 - 한규연; Kyu Yeon Hahn; 김현주; Hyun Ju Kim; 박혜정; Hye Jung Park; 김선욱; Sun Wook Kim; 장수연; Soo Yun Chang; 김범경; Beom Kyung Kim; et al. (The Korean journal of gastroenterology, 2014)
Advanced cancer patients with refractory ascites often do not respond to conventional treatments including dietary sodium restriction, diuretics, and repeated large volume paracentesis. In these patients, continuous peritoneal drainage by an indwelling catheter may be an effective option for managing refractory ascites with a relative low complication rate. Peritoneal catheter-induced complications include hypotension, hematoma, leakage, cellulitis, peritonitis, and bowel perforation. Although bowel perforation is a very rare complication, it can become disastrous and necessitates emergency surgical treatment. Herein, we report a case of a 57-year-old male with refractory ascites due to advanced liver cancer who experienced iatrogenic colonic perforation after peritoneal drainage catheter insertion and was treated successfully with endoscopic clipping. (Korean J Gastroenterol 2014;63:373-377)